CHEMICAL BURN ON CHILDREN PATIENT DUE TO IATROGENIC OF CRESOPHENE DURING ROOT CANAL TREATMENT - Ida Bagus Pramana Putra Manuaba; Mia Ayustina Prasetya; Luh Wayan Ayu Rahaswanti; Putu Imas Audina (Indonesian Journal of Dentistry, 2023)
Introduction: Chemical burns are injuries to the oral mucosa caused by the application of corrosive topical materials. Chemical trauma or chemical burns are one cause of mouth ulcers. Cutaneous and perioral skin chemical burn clinically, erythema, burning sensation, edema, desquamation, and ulcers. Case: A 6-year-old child patient complained of a burning sensation in the corner of the left lip during a treatment of root canal treatment using cresophene. Treatment: Patient was given a topical application of aloe vera extract dental gel, and was prescribed the same drug. Discussion: Cresophene is an antimicrobial agent used for infected root canal treatment. Cresophene is an agent antimicrobial class of phenol compounds, because it contains phenol, cresophene have antibacterial activity especially on group of gram positive bacteria. The clinical appearance of chemical burns depends on the severity of the tissue damage, the destructive properties, and mode of application of the causative agent. Aloe vera taken in a variety of dosage forms may be useful in accelerating the wound healing process and tend to raise the rate of success of healing and the rate of epithelialization in first and second burns.